Fermi surfaces, spin-mixing parameter, and colossal anisotropy of spin relaxation in transition metals from ab initio theory - Zimmermann, Bernd; Mavropoulos, Phivos; Long, Nguyen H.; Gerhorst, Christian-Roman; Blügel, Stefan; Mokrousov, Yuriy (PHYSICAL REVIEW B, 2016)
The Fermi surfaces and Elliott-Yafet spin-mixing parameter (EYP) of several elemental metals are studied by ab initio calculations. We focus first on the anisotropy of the EYP as a function of the direction of the spin-quantization axis {[}B. Zimmermann et al., Phys. Rev. Lett. 109, 236603 (2012)]. We analyze in detail the origin of the gigantic anisotropy in 5d hcp metals as compared to 5d cubic metals by band structure calculations and discuss the stability of our results against an applied magnetic field. We further present calculations of light (4d and 3d) hcp crystals, where we find a huge increase of the EYP anisotropy, reaching colossal values as large as 6000% in hcp Ti. We attribute these findings to the reduced strength of spin-orbit coupling, which promotes the anisotropic spin-flip hot loops at the Fermi surface. In order to conduct these investigations, we developed an adapted tetrahedron-based method for the precise calculation of Fermi surfaces of complicated shape and accurate Fermi-surface integrals within the full-potential relativistic Korringa-Kohn-Rostoker Green function method.